Promoting endothelialization of flow-diverting stents: a review. (2nd June 2020) - Panchendrabose, Kapilan; Muram, Sandeep; Mitha, Alim P
Abstract : Intracranial flow-diverting (FD) stents have revolutionized the treatment of intracranial aneurysms in recent years, but complications resulting from failed endothelialization can still occur. Approaches to promote endothelialization are understudied, but hold promise in mitigating both short- and long-term complications associated with FD stent insertion. The aim of this review is to highlight the various features of and modifications that have been made to FD stents in order to expedite endothelialization. More specifically, we focus on how endothelialization can be influenced by the stent design, wall apposition, surface modifications, and the inclusion of biological agents.